Diagnosis of Nonchariasis Diseases of The Tooth Hard Tissue Against The Background of Fatty Hepatosis - Axmedov Alibek Bahodirovich; Olimov Siddiq Sharifovich (Journal of Science in Medicine and Life, 2025)
Fatty hepatosis, or hepatic steatosis, is a common liver condition characterized by fat accumulation in hepatocytes and associated with metabolic dysfunction. While its systemic effects are well documented, its potential impact on oral structures — particularly tooth hard tissues — is poorly understood. This study explores the diagnostic features of non-carious lesions in the enamel and dentin of patients with fatty liver disease, aiming to uncover links between hepatic metabolic imbalance and tooth structural degradation. Through clinical dental evaluation, biochemical saliva testing, and hepatic function correlation, we identified a high prevalence of enamel erosion, hypersensitivity, and microcracks among patients with fatty hepatosis. The findings suggest that systemic lipid metabolism disorders may compromise the mineralization and resilience of dental hard tissues. This study highlights the importance of interdisciplinary screening approaches, especially in patients with chronic metabolic conditions, to ensure early detection and management of non-carious dental pathologies.